Identifying the administrator and teacher competencies according to the views of primary school administrators - Öznacar, Behçet (2019)
This study was conducted with the primary school administrators in the Turkish Republic of Northern Cyprus and the school administrators in Turkey; and it aimed to determine the views of school administrators regarding administrative processes. Case study method was adopted from qualitative research designs and participants were selected through snowball sampling from primary school administrators. Thus, the participants of the study consisted of 10 headmasters working in the primary schools of TRNC and 10 headmasters working in the primary schools of Turkey in the 2017-2018 academic year. Participants were asked open-ended and semi-structured questions in face-to-face interviews. The interviews were also audio-recorded. The collected data were analyzed through qualitative data analysis methods and analyzed data are presented through themes. When the responses of school administrators to the interview question are reviewed; it is observed teachers should be hard-working and successful and school climate should be enabling for organizational administrative processes are emphasized by the administrators.